Experimental study of coupling response characteristics of offshore monopiles, seabed, and waves in various sea conditions - Hailin Ye; Yaojiang Fan; Wenjing Bai; Chuwei Jiang (Scientific Reports)
Abstract As the global pursuit of renewable energy intensifies and the demand for offshore wind turbines rises, a comprehensive understanding of the coupling response characteristics of offshore monopiles, seabed, and waves in various sea conditions has become increasingly crucial. This paper reports on a wave flume experiment and seeks to contribute valuable insights by examining the coupling response of offshore monopiles, seabed, and waves exerting a relentless influence. The experimental results indicate that the impact of waves on monopiles is significant: there is greater pressure on the wave facing surface of the offshore piles than the other faces, and the pressure increases with increased wave height as well as the height of the monopile. The wave impact also gives rise to pile motion, squeezing the soil near the monopile and causing gradual pore water pressure around the monopile, and when the wave impact is strong enough, the monopile loses stability. Finally, the experimental results indicate significant differences in the coupling response characteristics of an offshore monopile, the seabed, and waves in various sea conditions. When the wave height was small, the pore water pressure attenuated quickly in the direction of the depth of the seabed; however, as the height and period of waves increased, when the test wave height was more than 18.6 cm and the period was more than 1.63 s, the dynamic pore water pressure around the monopile first decreased and then increased along the depth direction, which, generated by the wave impact, led to vibration and squeezing of the soil near the monopile leg. This indicates that the closer the pile bottom, the more intense the squeezing. By investigating this development across different sea conditions, this study provides a nuanced understanding that can inform the design of offshore monopiles in the face of various marine environmental challenges.